The Effect Of Inflation And The Bi Rate On Murabahah Financing At Bank Syariah Indonesia Tbk - Hastiani Nasution; Nursantri Yanti; Rahmi Syahriza (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the effect of inflation and the BI Rate on murabahah financing at Bank Syariah Indonesia. The data used in this study are secondary data obtained from the financial statements of Bank Syariah Indonesia, as well as macroeconomic data related to inflation and the BI Rate collected from Bank Indonesia through its official website. The results show that partially, inflation has a negative but not significant effect on murabahah financing. This indicates that an increase in inflation tends to reduce murabahah financing due to the decline in people's purchasing power; however, the effect is not statistically significant. Meanwhile, the BI Rate has a positive and significant effect on murabahah financing, indicating that changes in the BI Rate can influence the increase in the distribution of murabahah financing. Simultaneously, inflation and the BI Rate have a significant effect on murabahah financing. In addition, both variables have a relatively strong ability to explain the variation in murabahah financing, although there are still other factors outside the research model that also influence it.